Preface: The 2024 IEEE 6th Eurasia Conference on IoT, Communication and Engineering - Teen-Hang Meen; Chi-Ting Ho; Cheng-Fu Yang (Engineering Proceedings)
This volume presents the proceedings of the 2024 IEEE 6th Eurasia Conference on the IoT, Communication, and Engineering (IEEE ECICE 2024) [...]